Effectiveness of transcranial direct electrical stimulation in management of patellofemoral pain syndrome: A randomized controlled trial - Mahesh Sharma; Ramesh C. Patra; Shashikumar C. Govindappa (Journal of Family and Community Medicine)
Abstract: BACKGROUND: Patellofemoral pain syndrome is more common in young adults. This pain is treated by therapeutic modalities and exercises involving quadriceps. Transcranial direct current stimulation (tDCS) is a noninvasive method of relieving pain. This study assessed the tDCS together with knee strengthening exercises to treat patellofemoral pain syndrome. MATERIALS AND METHODS: Patients with patellofemoral pain were randomly put into two groups for a 6-week protocol. The experimental group was treated with transcranial direct electrical stimulation and knee muscles strengthening exercises, whereas the control group was treated with knee strengthening exercises only. Data for pain using Visual Analog Scale, disability or function using Anterior Knee Pain Score, and quality of life using The Knee Injury and Osteoarthritis Outcome Score was collected for both groups at baseline and in 6th week. Data for pain and disability were collected at baseline, in the 1st, 2nd, 4th and 6th week. Data were analyzed using SPSS; t-test for independent samples and ANOVA were used to compare mean scores between groups and various time intervals. RESULTS: The results showed that pain, disability, and Knee Injury and Osteoarthritis Outcome Score improved in both the groups. However, the experimental group demonstrated a more favorable outcome than the control group (P < 0.001). Pain scores varied significantly between time periods. From baseline to the 6th week, the mean score of the experimental group decreased from 7.75 > 5.42 > 1.40 > 0.38, respectively, and the mean score of the control group decreased from 7.68 > 7.30 > 2.98 > 0.64, respectively. At the 2nd and 4th weeks, there was a significant reduction in the pain score with a mean of 5.42 > 1.40 in the experimental group. CONCLUSION: Patellofemoral pain syndrome can be effectively treated with transcranial direct electrical stimulation combined with knee strengthening exercises, rather than with exercises only to strengthen knee muscles.